2015
DOI: 10.1002/mma.3523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of emergent carrying capacity in an eco‐epidemiological system

Abstract: The paper explores an eco-epidemiological model of a predator-prey type, where the prey population is subject to infection. The model is basically a combination of S-I type model and a Rosenzweig-MacArthur predator-prey model. The novelty of this contribution is to consider different competition coefficients within the prey population, which leads to the emergent carrying capacity. We explicitly separate the competition between non-infected and infected individuals. This emergent carrying capacity is markedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Apart from Allee parameter, the intra-class competition and inter-class competition can control chaos separately, which is not studied earlier. Recently, [66] have taken separate competition between non-infected and infected individuals. They observed that different intra-class and inter-class competition, which leads to the emergent carrying capacity can exhibit three species coexistence in an eco-epidemiological model, which is not possible in the case of explicit carrying capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from Allee parameter, the intra-class competition and inter-class competition can control chaos separately, which is not studied earlier. Recently, [66] have taken separate competition between non-infected and infected individuals. They observed that different intra-class and inter-class competition, which leads to the emergent carrying capacity can exhibit three species coexistence in an eco-epidemiological model, which is not possible in the case of explicit carrying capacity.…”
Section: Resultsmentioning
confidence: 99%
“…In explicit carrying capacity, competitive abilities for both the susceptible prey and infected prey are same but in emergent carrying capacity the competitive abilities for the susceptible prey and infected prey are different as in the presence of a disease, the infected prey population will not have the same competing ability as of susceptible one. [66] have shown that emergent carrying capacity can exhibit three species coexistence in an eco-epidemiological model.…”
Section: Introductionmentioning
confidence: 99%
“…Saifuddin et al, [6] modified Chattopadhyay and Arino model by assuming that the infected prey cannot reproduce, but both susceptible and infected are competing for the same resources. Here, the predator consumes both prey at the same rate.…”
Section: Introductionmentioning
confidence: 99%